High-Accuracy Pseudo-Random Code Laser Ranging Method Based on Data Shifting and Parameter Calibration of Phase Discriminator - Chaoyang Li; Fei Yang; Jianfeng Sun; Zhiyong Lu; Yu Zhou; Chenxiang Qian; Weibiao Chen (Photonics)
High-accuracy and high-precision inter-satellite ranging enhances the orbital accuracy of the Global Navigation Satellite System and facilitates Autonomous Navigation without requiring ground stations. This study proposes a novel phase discrimination method based on pseudo-random code phase modulation coherent laser ranging, which solves the problem of mutual restriction between ranging accuracy and ranging precision in the traditional method. The early–late correlation peaks are obtained via data shifting, while the early and late codes remain unchanged. The characteristic parameters of the early–late discriminator model are calibrated by the actual ranging system, which achieves enhanced ranging accuracy and precision simultaneously. Ground test results indicate that for the static target, the accuracy of the distance measurement is 0.56 mm, while the precision is 0.34 mm. The ranging accuracy of the proposed method has improved by a factor of 91 compared to the traditional method. For dynamic targets, the accuracies of the distance and speed measurements are 0.38 mm and 0.44 mm/s, respectively.